KEWENANGAN PEMERINTAH PROVINSI BALI DALAM PEMBANGUNAN PELABUHAN PARIWISATA SEBAGAI PENDUKUNG PARIWISATA BALI - Putri Kusuma Sanjiwani (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2015)
Bali Province is a province that relies on regional revenue in the tourism sector. Equitable development between North Bali South Bali require assistance through the form of government policy. One of the Bali provincial government policy is to break the waves of tourists is to build the port infrastructure development of tourism. Theory authority and policy concepts used to solve the problems concerning the form of government policy in the Bali Provincial Tourism Port infrastructure development as the carrying capacity of tourist distribution in promoting tourism in Bali. Normative research used in analyzing problems of government authority between state-owned enterprises and local goverment in accordance with regulations Indonesian republic. Explores the principle of decentralization adopted by the government system in Indonesia with a delegation of authority from the central government to local governments. Tourism ports is essential to be realized as one of the factors of sustainable tourism in Bali.